تقويم أداء المصارف باستخدام أدوات التحليل المالي دراسة ميدانية للمصرف الصناعي السوري - زيود, لطيف; الأمين, ماهر; المهندس, منيرة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر موضوع تقويم أداء المصارف ذا أهمية عالية في ظل التطورات التي يشهدها القطاع المصرفي, لأن القوائم المالية لم تعد قادرة على إعطاء صورة واضحة عن آلية العمل المصرفي, لذلك اعتبر التحليل المالي من أهم أساليب تقويم الأداء لأنه يوفر المؤشرات المالية التي تخدم عملية التخطيط والتقويم والرقابة, ويضع الأسس السليمة للتفكير في رسم الخطط المستقبلية. وتقويم أداء المصرف الصناعي يهدف إلى دراسة النشاط المنفذ, ويحدد نقاط القوة والضعف في النظام المحاسبي المصرفي, بحيث يوضح مدى كفاءة الإدارة في توظيف الموارد المالية المتوفرة لديها بالشكل الأمثل. وبناءً على هذه الدراسة توصلنا إلى عدة نتائج هامة , وقدمنا بعض المقترحات التي تؤدي إلى تطوير نظام العمليات في المصرف المدروس, وتنقله تدريجياً إلى المصرف الشامل. Evaluation of banks work is very important for technical developments of the banking sector to attend ,as the financial statement couldn't give a clear idea about the bank work mechanism any more. So financial analysis was considered the most important system of work evaluation, because it provides the financial indexes that serve planning, supervision and evaluation operations . It also lays sound foundation of future planning. An evaluation of Syrian industrial bank aims to study the real activity and to assign points of the weakness and strength of accounting system, and theshillsof its managment in investing financial resources in a perfect form. We have reached some important results, and offered the suggestions that develop the operations system in the studied bank shifting gradually to words the comprehensive bank.